Agri-voltaic system: crop production and photovoltaic-based electricity generation from a single land unit - Santra, P.; Singh, R. K.; Meena, H. M.; Kumawat, R. N; Mishra, D.; Jain, D.; Yadav, O. P. (Indian Farming, 2018)
Agri-voltaic system is designed and developed at Central Arid Zone Research Institute, Jodhpur through which electricity can be generated, crops can be cultivated at interspace area and rainwater can be harvested from top surface of PV-module. About 49% land area of a solar PV-installation system can be used to cultivate crops, which is otherwise left as fallow. Few of the selected crops are mungbean, mothbean, clusterbean, isabgol, cumin, and chickpea. Apart from these, medicinal plants e.g. Aloe vera, sonamukhi, sankhpuspi etc. can be grown. All these crops are generally low height crops and require less amount of water and thus are suitable for AVS. Apart from crop production, about 1,50,000 litre of rainwater on one acre can be harvested. The stored water can be used as supplemental irrigation to crops during rabi. Annual income from PV generated electricity has been estimated as Rupees 7,00,000 per acre, whereas cost involved for installation of such system is Rupees 55,00,000 and thus the breakeven period of the system is about 9-10 years.